Ideologi Al-Jazeera Arabic dalam wacana pemberitaan visi Saudi Muhammad bin Salman (analisis wacana model Fairclough) - Yuhandra, Muhammad Ghafary; Nugraha, Tubagus Chaeru; Lukman, Fahmy (Universitas Mulawarman, 2024)
This research aims to reveal the ideology of Al-Jazeera media and the social conditions that influence it through reporting on Muhammad bin Salman and the Saudi Vision 2030 on the Al-Jazeera Arabic news site. This research uses a qualitative descriptive method. The data in this research were analyzed using the Fairclough discourse analysis model. At the level of text analysis, the results of the study show that Al-Jazeera uses sharp and firm diction, namely by using phrases meaning “taukid” (strengthening), “laa” and “lam nafiyah” particles, sentences meaning “tasybih” (similarity) which have bad connotations, bad idioms, metaphorical expressions to show evil, causality to explain a situation, and the use of negative diction. At the level of discursive practice, Al-Jazeera creates news according to its target audience in the Middle East and Africa. At the sociocultural level, Al-Jazeera has an ideology, namely, representing the unrest of Middle Eastern society with the slogan, “The opinion and the other opinion.” Besides that, socio-political conditions in the Middle East and diplomatic relations between Saudi Arabia and Qatar influence Al-Jazeera in producing discourse about Saudi Arabia, especially Saudi Vision 2030.